Factoring Information into Returns - Easley, David; Hvidkjaer, Soeren; O’Hara, Maureen (Journal of Financial and Quantitative Analysis, 2010)
Abstract We examine the potential profits of trading on a measure of private information (PIN) in a stock. A zero-investment portfolio that is size-neutral but long in high PIN stocks and short in low PIN stocks earns a significant abnormal return. The Fama-French, momentum, and liquidity factors do not explain this return. However, significant covariation in returns exists among high PIN stocks and among low PIN stocks, suggesting that PIN might proxy for an underlying factor. We create a PIN factor as the monthly return on the zero-investment portfolio above and show that it is successful in explaining returns to independent PIN-size portfolios. We also show that it is robust to inclusion of the Pástor-Stambaugh liquidity factor and the Amihud illiquidity factor. We argue that information remains an important determinant of asset returns even in the presence of these additional factors.